Impact Evaluation Based on Buddhist Principles - Craig Russon; Karen Russon (The Evaluation Center at Western Michigan University, 2014)
Background:  This is one in a series of articles in which the authors attempt to relate Eastern philosophy to contemporary programme planning and evaluation.   Setting: Not applicable.   Purpose: The authors examine impact evaluation through the lens of Eastern Philosophy.   Subjects: Not applicable.   Research Design: Not applicable.   Data Collection and Analysis:  The authors examine the basic causal statements from the approach to impact evaluation commonly used by The World Bank and from Buddhist philosophy.  Second, they examine the econometric assumptions on which impact evaluation is often based and propose alternative Buddhist principles. Lastly, they speculate what impact evaluation might look like using the alternative principles that were identified.   Findings: Not applicable.   Conclusions:  There is no such thing as impact in and of itself.  Rather, a combination of conditions comes together in a certain way, at a certain time, and we call it an impact. Impact is, therefore, the result of conditionality (Salzberg, & Goldstein, 2001).   Evaluation that examined the conditionality of impact would be in a position to make statements about patterns of relationships.  Instead of experimental and quasi-experimental approaches, the Insight Evaluation approach (Russon and Russon, 2011) might be more appropriate.